Characterization, Thermal Stability and Antimicrobial Evaluation of the Inclusion Complex of Litsea cubeba Essential Oil in Large-Ring Cyclodextrins (CD9–CD22) - Chuan Cao; Peng Xie; Yibin Zhou; Jing Guo (Foods, 2023)
Food safety issues are becoming increasingly important as a result of contamination with foodborne pathogenic bacteria. Plant essential oil is a safe and non-toxic natural antibacterial agent that can be used to develop antimicrobial active packaging materials. However, most essential oils are volatile and require protection. In the present study, LCEO and LRCD were microencapsulated through coprecipitation. The complex was investigated using GC-MS, TGA, and FT-IR spectroscopy. According to the experimental results, it was found that LCEO entered the inner cavity of the LRCD molecule and formed a complex with LRCD. LCEO had a significant and broad-spectrum antimicrobial effect against all five microorganisms tested. At 50 °C, the microbial diameter of the essential oil and its microcapsules showed the least change, indicating that this essential oil has high antimicrobial activity. In research on microcapsule release, LRCD has proven to be a perfect wall material for controlling the delayed release of essential oil and extending the duration of antimicrobial activity. LRCD effectively extends antimicrobial duration by encasing LCEO, thus improving its heat stability and antimicrobial activity. The results presented here indicate that LCEO/LRCD microcapsules can be further utilized in the food packaging industry.